Interaction of diabetes and smoking on stroke: a population-based cross-sectional survey in China - Lou, Heqing; Dong, Zongmei; Zhang, Pan; Shao, Xiaoping; Li, Ting; Zhao, Chunyan; Zhang, Xunbao; Lou, Peian (BMJ open, 2018)
ObjectivesDiabetes and smoking are known independent risk factors for stroke; however, their interaction concerning stroke is less clear. We aimed to explore such interaction and its influence on stroke in Chinese adults.DesignCross-sectional study.SettingCommunity-based investigation in Xuzhou, China.ParticipantsA total of 39 887 Chinese adults who fulfilled the inclusion criteria were included.MethodsParticipants were selected using a multistage stratified cluster method, and completed self-reported questionnaires on stroke and smoking. Type 2 diabetes mellitus (DM2) was assessed by fasting blood glucose or use of antidiabetic medication. Interaction, relative excess risk owing to interaction (RERI), attributable proportion (AP) and synergy index (S) were evaluated using a logistic regression model.ResultsAfter adjustment for age, sex, marital status, educational level, occupation, physical activity, body mass index, hypertension, family history of stroke, alcohol use and blood lipids, the relationships between DM2 and stroke, and between smoking and stroke, were still significant: ORs were 2.75 (95% CI 2.03 to 3.73) and 1.70 (95% CI 1.38 to 2.10), respectively. In subjects with DM2 who smoked, the RERI, AP and S values (and 95% CIs) were 1.80 (1.24 to 3.83), 0.52 (0.37 to 0.73) and 1.50 (1.18 to 1.84), respectively.ConclusionsThe results suggest there are additive interactions between DM2 and smoking and that these affect stroke in Chinese adults.